In vitro evaluation of agro-industrial by-products in diets for cattle - Krizsan, Sophie Julie; Franco, Marcia; Rinne, Marketta; Ramin, Mohammad; Fatehi, Farhang (Scientific Agricultural Society of Finland, 2025)
The objective of this in vitro batch culture study was to evaluate various agro-industrial by-products as feeds for cattle. In Experiment 1, a basal diet composed of grass silage and barley grain was replaced by additional barley grain, palm kernel cake (PKC), beet molasses (M), wheat bran (WB), or sugar beet pulp (SBP) at two levels of dietary supplementation. In Experiment 2, soybean meal (SBM) was compared with heat-treated rapeseed meal, dried distillers´ grains (DDG), rapeseed cake (RSC), and rapeseed meal (RSM) at two levels of dietary protein concentration in diets based on grass silage supplemented with barley grain or SBP. Propionate and branched chain volatile fatty acids decreased, and CH4 production increased when energy by-products of higher fibre content replaced barley grain. Diets incorporating PKC and WB were less fermentable, while M and SBP did not alter digestibility when replacing barley. Generally, incremental levels of protein in Experiment 2 linearly increased digestibility, utilisable crude protein (uCP), isobutyrate and valerate in vitro. Utilisable crude protein increased for all by-products that replaced SBM, except for RSM in diets including SBP. There was a positive linear effect of by-product level on uCP and valerate, and a negative linear effect for acetate. Diet digestibility was equivalent for DDG and SBM in diets composed with barley as well as SBP. Overall, by-products provided more uCP than diets supplemented with SBM. However, the intestinal digestibility of uCP of the different feeds can vary. In vivo production experiments are needed to fully assess the potential of in vitro evaluated by-products as widely applicable alternative feeds in diets for cattle.
Keywords: barley; by-products; methane; protein; soybean meal; utilisable crude protein